Enterprise Management in Emergency and Environmental Disaster Situations (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Management of the enterprise is a systematic influence on the work of all its constituent elements, the purpose of which is to organize coordinated work and, as a result, profit. The goal of enterprise management is to achieve coordinated work of all departments to achieve maximum efficiency. The essence of enterprise management is to establish this consistency. Since the enterprise is a complex production system based on components such as fixed assets, material, financial and labor resources, the task of management is to use these resources as efficiently as possible. At the output, it is necessary to obtain a high-quality competitive product that will help further development of production [1].